THE INFLUENCE OF MODEL A DEMONSTRATION INTERACTIVE WITH MEDIA PROPS AGAINST THE CRITICAL THINKING SKILLS AND LEARNING MOTIVATION OF HIGH SCHOOL STUDENTS. - Hafizhasando, Ramajid; Tahir, Andi; Supriyadi, Supriyadi (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
The research was conducted in SMA Negeri 2 Kotabumi North Lampung District school year 2017/2018. This study aims to Determine how much influence the use of Interactive Demonstration models with medi props against critical thinking skills and learning motivation grade XI. This type of research is quantitative research methodsExperimental quasy design.The population in this study is a class XI IPA 1 and XI IPA 2, means of the data collection in the form of tests, non-test, and documentation.Based on the results Obtained by the achievement for the critical thinking skills of the experimental class average value (79), while the control class average value (67). For motivation to learn Obtained experimental class props percentage (86%) while the percentage for the class gained control of (77%). Based on correlation test of significance of 0.009> 0.05, then there is a significant correlation. The results Showed that the effect of the media aided Interactive Demonstration models props significant effect on critical thinking skills and learning motivation.